2012
DOI: 10.5923/j.ajmms.20120201.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium on Carbimazole-Induced Histopathological and Histochemical Alterations in Prostate of Albino Rats

Abstract: Carbimazole is an antithyroid drug used in treatment of hyperthyroidism. The present study is undertaken to evaluate the effect of carbimazole in prostate of albino rats and the ameliorative role of selenium. Treating rats with carbimazole(1.35mg/Kg b.w) daily for 8 weeks caused distinct histological alterations in prostate gland compared with control group. The epithelial cells of prostatic acini exhibited degeneration. Hyperplasia were projected into the lumens of the prostatic acini or to the outside stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Similar results were described previously and were attributed to increased permeability of the cell membrane in response to cell injury leading to an increase in the volume of intracellular water as it sufficiently accumulates within the cell and produces cytoplasmic vacuolation [3]. It was suggested that injurious agents may also interfere with the ATP-dependent sodium-potassium pump by increasing the permeability of the cell membrane to sodium, thereby exceeding the capacity of the pump to extrude sodium, or damaging the pump directly.…”
Section: Recommendationsmentioning
confidence: 59%
See 2 more Smart Citations
“…Similar results were described previously and were attributed to increased permeability of the cell membrane in response to cell injury leading to an increase in the volume of intracellular water as it sufficiently accumulates within the cell and produces cytoplasmic vacuolation [3]. It was suggested that injurious agents may also interfere with the ATP-dependent sodium-potassium pump by increasing the permeability of the cell membrane to sodium, thereby exceeding the capacity of the pump to extrude sodium, or damaging the pump directly.…”
Section: Recommendationsmentioning
confidence: 59%
“…Previous studies have proven that oral administration of GA3 induces different biochemical and histochemical changes in the liver of treated rats in the form of early increase followed by late decrease in liver enzymes and marked reduction in total carbohydrate and total protein content in hepatocytes [3].…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Intraepithelial vacuolization may be considered as a manifestation of testicular tubules' atrophy [87]. Sakr et al [66] attributed the vacuolated cytoplasm of spermatogenic cells to lipid peroxidation causing damage to the cell membrane and membranes of the cell organelles with subsequent increase in their permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Group II rats were given 1 mL of ginger aqueous extract orally by a stomach tube (24 mg/mL) daily for three and six weeks. Group III rats were orally given carbimazole 1.35 mg/kg bw, equivalent to the therapeutic dose for human dissolved in distilled water by stomach tube [19]. Group IV rats were orally given 24 mg/mL of ginger extract by stomach tube followed by carbimazole (1.35 mg/kg bw) for three and six weeks.…”
Section: Animal Models and Groups Treatmentsmentioning
confidence: 99%